SARM1 deficiency promotes rod and cone photoreceptor cell survival in a model of retinal degeneration - Monaghan, Michael; Doyle, Sarah; Humphries, Peter; Carty, Michael; Bowie, Andrew; Campbell, Matthew; Humphries, Marian (My University, 2020)
Retinal degeneration is the leading cause of incurable blindness worldwide and is characterised by progressive loss of light-sensing photoreceptors in the neural retina. SARM1 is known for its role in axonal degeneration, but a role for SARM1 in photoreceptor cell degeneration has not been reported. SARM1 is known to mediate neuronal cell degeneration through depletion of essential metabolite NAD and induction of energy crisis. Here, we demonstrate that SARM1 is expressed in photoreceptors, and using retinal tissue explant, we confirm that activation of SARM1 causes destruction of NAD pools in the photoreceptor layer. Through generation of rho−/−sarm1−/− double knockout mice, we demonstrate that genetic deletion of SARM1 promotes both rod and cone photoreceptor cell survival in the rhodopsin knockout (rho−/−) mouse model of photoreceptor degeneration. Finally, we demonstrate that SARM1 deficiency preserves cone visual function in the surviving photoreceptors when assayed by electroretinography. Overall, our data indicate that endogenous SARM1 has the capacity to consume NAD in photoreceptor cells and identifies a previously unappreciated role for SARM1-dependent cell death in photoreceptor cell degeneration.
PUBLISHED
Keywords: photoreceptor cell degeneration; Retinal degeneration; incurable blindness